Clinical Spinoza : integrating his philosophy with contemporary therapeutic practice - Miller, Ian S. (New York : Routledge, 2022)
"Discovering Spinoza's early modern psychology some 35 years into his own clinical practice, Ian Miller now gives shape to this connection through a close reading of Spinoza's key philosophical ideas. With a rigorous and expansive analysis of Spinoza's Ethics in particular, Miller explores how Spinozan thought simultaneously empowered the original conceptual direction of psychoanalytic thinking, and anticipated the field's contemporary theoretical dimensions. Miller offers a detailed overview of the philosopher's psychoanalytic reception from the early work of German-language psychoanalytic thinkers, such as Freud and Andreas Lou-Salome, forward into its Anglophone reception, influencing both mid-century humanistic American psychoanalysis as well as anticipating thinkers such as Bion and Winnicott. Covering key concepts in psychoanalytic theory and clinical practice, this book demonstrates how knowledge of Spinoza's philosophical work can help to both illuminate and improve modern psychoanalytic therapies"--
Keywords: Spinoza, Benedictus de, -- 1632-1677.; Psychoanalysis and philosophy; Psychology and philosophy; PHILOSOPHY / General; PSYCHOLOGY / Movements / Psychoanalysis; PSYCHOLOGY / Mental Health